Method for producing anisotropic magnetic powder

By precisely mixing iron oxide with rare earth oxides and applying heat treatment, reduction, and nitriding processes, the method produces anisotropic magnetic powder with superior magnetic properties, addressing issues of particle size and impurity presence in existing methods.

JP2025010610AInactive Publication Date: 2025-01-22NICHIA CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024186874
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2024-10-23
Publication Date
2025-01-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for producing anisotropic magnetic powder do not achieve optimal magnetic properties due to issues with particle size, mixing uniformity, and impurity presence, leading to reduced magnetic performance.

Method used

A method involving the precise mixing of iron oxide particles with specific rare earth oxides, followed by heat treatment, reduction, and nitriding processes to form alloy particles, which are then nitrided to produce anisotropic magnetic powder with improved magnetic properties.

Benefits of technology

The method results in anisotropic magnetic powder with enhanced magnetic properties, including higher residual magnetic flux density, coercive force, and squareness ratio, by controlling particle size, mixing uniformity, and minimizing impurities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010610000002
    Figure 2025010610000002
  • Figure 2025010610000003
    Figure 2025010610000003
  • Figure 2025010610000004
    Figure 2025010610000004
Patent Text Reader

Abstract

To provide a method for producing an anisotropic magnetic powder excellent in magnetic properties.SOLUTION: There is provided a method for producing an anisotropic magnetic powder including the steps of: mixing iron oxide particles having an average particle diameter of 0.1 μm or more and 0.4 μm or less with oxide particles of R having an average particle diameter of 0.5 μm or more and 0.8 μm or less (R is at least one kind selected from the group consisting of Sc, Y, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Tm, Lu) to obtain a mixture; heat-treating the mixture under a reducing gas atmosphere to obtain partial oxide; obtaining alloy particles by reducing the partial oxide; and obtaining an anisotropic magnetic powder by nitriding the alloy particles.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing anisotropic magnetic powder. [Background technology]

[0002] Patent Document 1 discloses a method for producing anisotropic magnetic powder, in which an acidic aqueous solution of rare earth elements and iron is dropped into an alkaline solution to obtain a coprecipitate, which is then oxidized and then reduced and nitrided.

[0003] Patent Document 2 discloses a method for producing anisotropic magnetic powder by reducing a mixture of iron oxide particles and oxide particles of a rare earth element by hydrogen heat treatment, further reducing the mixture to obtain an alloy, and then nitriding the alloy. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2014-080653 A [Patent Document 2] JP 2010-270379 A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a method for producing anisotropic magnetic powder having excellent magnetic properties. [Means for solving the problem]

[0006] The method for producing the anisotropic magnetic powder of the present invention comprises the steps of: A step of mixing iron oxide particles having an average particle size of 0.1 μm or more and 0.4 μm or less with oxide particles of R (R is at least one selected from the group consisting of Sc, Y, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Tm, and Lu) having an average particle size of 0.5 μm or more and 0.8 μm or less to obtain a mixture; a step of heat-treating the mixture in a reducing gas atmosphere to obtain a partial oxide; obtaining alloy particles by reducing the partial oxide; and The method includes a step of obtaining an anisotropic magnetic powder by nitriding the alloy particles. Effect of the Invention

[0007] It is possible to provide a method for producing anisotropic magnetic powder having excellent magnetic properties. [Brief description of the drawings]

[0008] [Figure 1] 1 is an electron microscope image of the anisotropic magnetic powder obtained in Example 1. [Diagram 2] 3 is an electron microscope image of the anisotropic magnetic powder obtained in Comparative Example 1. [Diagram 3] 4 is an electron microscope image of the anisotropic magnetic powder obtained in Comparative Example 2. [Figure 4] 4 is an electron microscope image of the anisotropic magnetic powder obtained in Comparative Example 3. [Diagram 5] 4 is an electron microscope image of the anisotropic magnetic powder obtained in Comparative Example 4. [Figure 6] 1 is an electron microscope image of the anisotropic magnetic powder obtained in Comparative Example 5. [Figure 7] 1 is an electron microscope image of the anisotropic magnetic powder obtained in Comparative Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the embodiments of the present invention will be described in detail. However, the embodiments shown below are examples for embodying the technical idea of ​​the present invention, and the present invention is not limited to the following. In this specification, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved. Furthermore, a numerical range indicated using "~" indicates a range including the numerical values ​​written before and after "~" as the minimum and maximum values, respectively. Furthermore, when a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.

[0010] The method for producing the anisotropic magnetic powder in this embodiment is as follows: A step of mixing iron oxide particles having an average particle size of 0.1 μm or more and 0.4 μm or less with oxide particles of R (R is at least one selected from the group consisting of Sc, Y, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Tm, and Lu) having an average particle size of 0.5 μm or more and 0.8 μm or less to obtain a mixture (mixing step); A step of obtaining a partial oxide by heat-treating the mixture in a reducing gas atmosphere (pretreatment step); A step of obtaining alloy particles by reducing the partial oxide (reduction step); and A step of obtaining anisotropic magnetic powder by nitriding the alloy particles (nitriding step). According to this embodiment, by mixing iron oxide particles having the above-mentioned average particle size with oxide particles of R (R is at least one selected from the group consisting of Sc, Y, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Tm, and Lu) having the above-mentioned average particle size, it is possible to reduce uneven distribution of the iron oxide particles and the oxide particles of R in the mixture, which is believed to improve the magnetic properties.

[0011] <Mixing process> The mixing step is a step of mixing iron oxide particles with oxide particles of R (R is at least one selected from the group consisting of Sc, Y, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Tm, and Lu).

[0012] The average particle size of the iron oxide particles is 0.1 μm or more and 0.4 μm or less, preferably 0.13 μm or more and 0.35 μm or less, and more preferably 0.15 μm or more and 0.25 μm or less. If the average particle size exceeds 0.4 μm, the magnetic properties tend to deteriorate due to a decrease in the mixability with the oxide particles of R. If the average particle size is less than 0.1 μm, the iron oxide particles contain a large amount of impurities, which act as a flux during the heat treatment described below to generate coarse particles, and the magnetic properties tend to deteriorate. Here, the average particle size in the present invention is a particle size measured under dry conditions using a laser diffraction type particle size distribution measuring device.

[0013] The oxide particles of R are at least one oxide selected from the group consisting of Sc, Y, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Tm, and Lu, but from the viewpoint of magnetic properties, Sm2O3, which is an oxide of Sm, is preferred. The average particle size of the oxide particles of R is 0.5 μm or more and 0.8 μm or less, preferably 0.53 μm or more and 0.75 μm or less, and more preferably 0.55 μm or more and 0.70 μm or less. If the average particle size is less than 0.5 μm, hydration reaction is likely to occur, which causes rapid heat generation, making handling difficult, and if the average particle size exceeds 0.8 μm, the mixability with iron oxide particles decreases, and abnormal growth of iron oxide particles is likely to occur in the pretreatment process described below, which tends to deteriorate the magnetic properties.

[0014] The average particle size of the oxide particles of R is preferably 4 times or less than the average particle size of the iron oxide particles. If it exceeds 4 times, the mixing property of the iron oxide particles and the oxide particles of R tends to deteriorate.

[0015] The amount of R oxide particles is preferably 32.2 to 36.8 parts by weight, more preferably 33.2 to 35.3 parts by weight, per 100 parts by weight of iron oxide particles. If it exceeds 36.8 parts by weight, the proportion of R-rich nonmagnetic phase increases and magnetic properties tend to deteriorate, whereas if it is less than 32.2 parts by weight, α-Fe is generated and magnetic properties, especially coercivity, tend to deteriorate.

[0016] Examples of iron oxide particles include magnetite (Fe3O4) and hematite (Fe2O3). Among these, magnetite is preferred because it is easily magnetically agglomerated and allows solid-liquid separation even in fine particles.

[0017] As the iron oxide particles, commercially available ones may be used as long as they are within the above-mentioned particle size range. For example, magnetite iron oxide particles can be synthesized by blowing an oxygen-containing gas such as air into a slurry containing a precipitate of iron hydroxide (Fe(OH)2) prepared by adding an alkaline agent to an aqueous iron solution under conditions of a temperature of 70 to 90°C and a pH of 7.0 to 8.5 (wet oxidation method). As an iron raw material for producing the iron hydroxide precipitate, iron sulfate can be mentioned in terms of ease of availability. As the alkaline agent, an alkali metal hydroxide or ammonia can be mentioned, but an alkali metal hydroxide is preferable, and sodium hydroxide is particularly more preferable in terms of its low manufacturing cost and environmental load. In addition, according to the wet oxidation method, recrystallization occurs when magnetite iron oxide particles are synthesized from the precipitate of iron hydroxide particles, so it is easy to reduce the concentration of residual alkali metals described below.

[0018] The alkali metal concentration in the iron oxide particles is preferably 200 ppm or less, more preferably 100 ppm or less. If the alkali metal concentration in the iron oxide particles exceeds 200 ppm, it acts as a flux during the reduction step described below, and coarse particles are generated, which tends to deteriorate the magnetic properties. In addition, in the above-mentioned wet oxidation method, the alkali metal concentration can be reduced by penetrating and washing the slurry of the synthesized magnetite iron oxide particles with pure water. The penetrating and washing here refers to an operation of washing the dehydrated cake in the filter without opening the filter.

[0019] Mixing of iron oxide particles and oxide particles of R can be performed by mixing a slurry containing iron oxide particles with a slurry containing oxide particles of R. Mixing may be performed by stirring, but precision mixing is preferred because it can reduce uneven distribution of iron oxide particles and oxide particles of R in the mixture in a small area (4 μm). Methods of precision mixing include mixing using a bead mill and mixing using a beadless line mixer. When using a bead mill, the bead diameter is preferably 0.05 mm or more and 0.5 mm or less.

[0020] The coefficient of variation (CV) of the mixture distribution, which indicates the uneven distribution of iron oxide particles and oxide particles of R in the mixture, is preferably 23% or less, more preferably 22% or less, and particularly preferably 21% or less. If the coefficient of variation exceeds 23%, the magnetic properties of the anisotropic magnetic powder tend to deteriorate. The coefficient of variation of the mixture distribution is obtained by taking a backscattered electron image of the mixture at 5000x magnification, dividing the image into squares with corners equivalent to 4 μm, calculating the area ratio of iron oxide and oxide particles of R for each square from these squares, and calculating the variation in the area ratio.

[0021] After mixing the iron oxide particles and the oxide particles of R, it is preferable to wash and dry the mixture. Washing can be performed with pure water until the effluent conductivity becomes 30 μS / cm or less, and drying can be performed by spray drying at about 200° C. to 250° C.

[0022] <Addition of calcium hydroxide> In addition to the iron oxide particles and the oxide particles of R, calcium hydroxide may be added. When calcium hydroxide is added to a mixture of iron oxide particles and oxide particles of R, the presence of calcium hydroxide between the iron oxide particles can suppress contact between the iron oxide particles. As a result, sintering between the iron oxide particles can be suppressed, and the dispersibility of the anisotropic magnetic powder is improved. Calcium hydroxide is a substance that is resistant to high temperature heating in the pretreatment step, reduction step, and nitriding step, reduction by reducing gases, and reduction by metallic Ca, and is preferable because it does not generate gases other than water in the pretreatment step and is easy to remove in the water washing step.

[0023] The average particle size of calcium hydroxide is preferably 0.05 μm to 0.8 μm, more preferably 0.3 μm to 0.5 μm. If the average particle size exceeds 0.8 μm, the effect of suppressing sintering of iron oxide particles tends to decrease, and if it is less than 0.05 μm, it is difficult to produce by grinding with a bead mill.

[0024] The average particle size of calcium hydroxide is preferably 4 times or less the average particle size of iron oxide particles. If it exceeds 4 times, the mixing property of iron oxide particles and oxide particles of R tends to deteriorate.

[0025] When calcium hydroxide is added, the amount is preferably 8 parts by weight to 48 parts by weight, and more preferably 18 parts by weight to 32 parts by weight, per 100 parts by weight of iron oxide particles. If it exceeds 48 parts by weight, the particle size of the magnetic powder becomes small and the magnetic properties, especially the residual magnetization, tend to decrease, while if it is less than 8 parts by weight, the effect of suppressing sintering of the iron oxide particles tends to decrease.

[0026] The calcium hydroxide may be in a state where it is mixed with the iron oxide particles before the pretreatment step, and the mixing method is not particularly limited, but it is preferable to mix a slurry of calcium hydroxide with a slurry containing iron oxide particles and oxide particles of R. The mixing may be performed by stirring and mixing, but precision mixing is preferable because it can reduce uneven distribution of the iron oxide particles, oxide particles of R, and calcium hydroxide in the mixture.

[0027] <Pretreatment process> The pretreatment step is a step in which a mixture of iron oxide particles and R oxide particles is heat-treated in a reducing gas atmosphere to obtain a partial oxide in which most of the iron oxide contained therein is reduced.

[0028] The reducing gas is appropriately selected from hydrocarbon gases such as hydrogen (H2), carbon monoxide (CO), and methane (CH4), but hydrogen gas is preferred from the viewpoint of cost. The flow rate of the gas is appropriately adjusted within a range in which oxides do not fly off. The heat treatment temperature in the pretreatment step (hereinafter, pretreatment temperature) is preferably 300°C or higher and 950°C or lower, more preferably 400°C or higher, further preferably 750°C or higher, and preferably lower than 900°C. When the pretreatment temperature is 300°C or higher, the reduction of iron oxide proceeds efficiently. Furthermore, when the pretreatment temperature is 950°C or lower, particle growth and segregation of iron particles generated by reduction are suppressed, and the desired particle size can be maintained. Furthermore, when hydrogen is used as the reducing gas, it is preferable to adjust the thickness of the oxide layer used to 20 mm or less, and further adjust the dew point in the reactor to -10°C or less.

[0029] <Reduction process> The reduction step is a step of reducing the obtained partial oxide, for example, by mixing the partial oxide with metallic calcium and heat-treating it in an atmosphere of an inert gas other than nitrogen, such as argon, or in vacuum, to obtain alloy particles containing iron and R.

[0030] The oxide is reduced by contacting with calcium melt or calcium vapor. The heat treatment temperature in the reduction step (hereinafter, reduction temperature) is in the range of 700°C to 1200°C, and preferably in the range of 800°C to 1100°C. From the viewpoint of carrying out the reduction reaction more uniformly, the heat treatment can be performed for a time period in the range of 10 minutes to 10 hours, and preferably in the range of more than 10 minutes to 2 hours.

[0031] Metallic calcium is used in the form of granules or powder, and the particle size is preferably 10 mm or less. This makes it possible to more effectively suppress necking of particles during the reduction reaction. Metallic calcium can be added in an amount of 1.1 to 3.0 times the reaction equivalent (the stoichiometric amount required to reduce rare earth oxides, including the amount required to reduce iron oxides), and is preferably added in an amount of 1.5 to 2.5 times the reaction equivalent.

[0032] In the reduction step, a disintegration promoter can be used as necessary together with metallic calcium as a reducing agent. This disintegration promoter is used appropriately to promote disintegration and granulation of the product in the water washing step described below, and examples thereof include alkaline earth metal salts such as calcium chloride, and alkaline earth oxides such as calcium oxide. These disintegration promoters are used in a ratio of 1% by mass to 30% by mass, preferably 5% by mass to 30% by mass, based on the rare earth oxide used as the rare earth source.

[0033] <Nitriding process> The nitriding process is a process for obtaining anisotropic magnetic particles by nitriding the alloy particles obtained in the reduction process. Since a porous sintered mass is obtained in the reduction process, the nitriding process can be performed uniformly by immediately subjecting the sintered mass to heat treatment in a nitrogen atmosphere without pulverization.

[0034] The heat treatment temperature in the nitriding treatment of the alloy particles (hereinafter, nitriding temperature) is 300° C. to 600° C., particularly 400° C. to 550° C., and is performed by replacing the atmosphere with a nitrogen atmosphere within this temperature range. The heat treatment time may be set so that the nitriding of the alloy particles is sufficiently uniform, for example, about 2 hours to 30 hours.

[0035] <Water washing process> The water washing step is a step in which the sintered body obtained in the nitriding step is put into cold water to disintegrate the sintered body and separate the anisotropic magnetic particles from impurities. The product obtained after the nitriding step may contain, in addition to the magnetic particles, by-produced CaO, unreacted metallic calcium, etc., and may be in the form of a composite sintered mass. In this case, the product may be put into cooling water to separate the CaO and metallic calcium from the magnetic particles as a calcium hydroxide (Ca(OH)2) suspension. Furthermore, the remaining calcium hydroxide may be sufficiently removed by washing the magnetic particles with acetic acid or the like. When the product is put into water, the oxidation of metallic calcium by water and the hydration reaction of by-produced CaO cause the composite sintered mass reaction product to disintegrate, i.e., to become fine powder. In addition, if calcium hydroxide is added in the mixing step, it can be removed in the water washing step. When performing surface treatment, a phosphoric acid solution may be added as a surface treatment agent in a range of 0.10% by mass to 10% by mass as PO4 relative to the magnetic particle solid content obtained in the nitriding step. After appropriate separation from the solution and drying, anisotropic magnetic powder is obtained.

[0036] The anisotropic magnetic powder obtained in the above manner is typically represented by the following general formula: R x Fe (100-x-y) N y (In the formula, R represents at least one selected from the group consisting of Sc, Y, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Tm, and Lu, x is 3 or more and 30 or less, and y is 5 or more and 15 or less.) From the viewpoint of magnetic properties, R is preferably Sm.

[0037] In the general formula, x is specified to be 3 to 30 because, if it is less than 3, the unreacted portion of the iron component (α-Fe phase) separates, the coercive force of the nitride decreases, and the magnet becomes unusable, and if it exceeds 30, at least one element selected from the group consisting of Sc, Y, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Tm, and Lu precipitates, the magnetic powder becomes unstable in the air, and the residual magnetic flux density decreases. Also, y is specified to be 5 to 15 because, if it is less than 5, almost no coercive force is exhibited, and if it exceeds 15, nitrides of at least one element selected from the group consisting of Sc, Y, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Tm, and Lu and of iron itself are formed.

[0038] <Composite materials> A composite material can be produced from the anisotropic magnetic powder of the present invention and a resin. By including the anisotropic magnetic powder of the present invention, a composite material having high magnetic properties can be formed.

[0039] The resin contained in the composite material may be either a thermosetting resin or a thermoplastic resin, but is preferably a thermoplastic resin. Specific examples of the thermoplastic resin include polyphenylene sulfide resin (PPS), polyether ether ketone (PEEK), liquid crystal polymer (LCP), polyamide (PA), polypropylene (PP), polyethylene (PE), etc.

[0040] When obtaining a composite material, the mixing ratio of the anisotropic magnetic powder and the resin (resin / magnetic powder) is preferably 0.10 or more and 0.15 or less, and more preferably 0.11 or more and 0.14 or less.

[0041] The composite material can be obtained, for example, by mixing anisotropic magnetic powder and a resin at 280° C. or higher and 330° C. or lower using a kneader.

[0042] <Bonded magnet> The composite material described above can be used to manufacture a bonded magnet. Specifically, for example, the composite material can be heat-treated while aligning the axis of easy magnetization in an orienting magnetic field (orientation process), and then pulse-magnetized in a magnetizing magnetic field (magnetization process) to obtain a bonded magnet.

[0043] The heat treatment temperature in the orientation step is, for example, preferably 90° C. or more and 200° C. or less, and more preferably 100° C. or more and 150° C. or less. The magnitude of the orientation magnetic field in the orientation step can be, for example, 720 kA / m. The magnitude of the magnetizing magnetic field in the magnetization step can be, for example, 1500 kA / m or more and 2500 kA / m or less. EXAMPLES

[0044] Examples will be described below. Unless otherwise specified, "%" is by weight.

[0045] (1) Example 1 (Mixing process) 2000 kg of ferrous sulfate (FeSO4) with an iron concentration of 8% was added to 988 kg of pure water, and 25% caustic soda was added while stirring until the pH reached 10.5 to create an iron hydroxide slurry. After heating this iron hydroxide slurry to 70-80°C, aeration was performed while controlling the pH to 7.5-8.5, and a slurry containing 221.3 kg of magnetite (Fe3O4) with an average particle size of 0.20 μm was created as iron oxide particles.

[0046] While stirring 74.7 kg of pure water, 74.7 kg of samarium oxide (Sm2O3) was dissolved little by little to avoid aggregation, to prepare a samarium oxide slurry. The samarium oxide particles in the slurry were then pulverized until the average particle size was 0.70 μm.

[0047] The samarium oxide slurry was added to the magnetite slurry and stirred, and precision mixing was performed using a bead mill (bead diameter 0.1 mm) to produce an oxide slurry in which iron and samarium were mixed uniformly at a micro level. This oxide slurry was washed with pure water until the drainage conductivity was 30 μS / cm or less, and then dehydrated to a solid concentration of 30 to 50%, thereby increasing the concentration of the slurry. The increased concentration of the oxide slurry was pumped and spray-dried at approximately 250°C, yielding 296 kg of black Fe, Sm mixed oxide.

[0048] (Pretreatment process) The oxide powder (296 kg) obtained above was reduced in a hydrogen reduction furnace at about 800° C. to reduce the oxygen concentration in the powder to 5.8 mass % or less. 228 kg of hydrogen-reduced powder was recovered.

[0049] (Reduction process) Metallic calcium (particle size approximately 6 mm) was prepared in an amount 2.25 times equivalent to the amount of oxygen contained in the powder obtained in the above pretreatment process, and mixed with the hydrogen-reduced powder. Specifically, 103.8 g of hydrogen-reduced powder and 29.8 g of metallic calcium were mixed, press-molded, and placed in a furnace. After evacuating the furnace, argon gas (Ar gas) was introduced. The temperature was raised to 1030°C and held there for 2 hours to obtain Fe-Sm-M alloy particles.

[0050] (nitriding process) After the reduction step, the mixture was cooled to 100° C., then evacuated to a vacuum. While introducing nitrogen gas, the temperature was raised to 430° C. and maintained at that temperature for 23 hours to obtain a reaction product containing anisotropic magnetic powder.

[0051] (Water washing process) The lump-shaped reaction product obtained in the nitriding step was added to 3 kg of pure water and stirred for 30 minutes. After standing, the supernatant was drained by decantation. The process of adding to pure water, stirring and decantation was repeated 10 times. Next, 4.0 g of 99.9% acetic acid was added and stirred for 15 minutes. The obtained slurry was subjected to solid-liquid separation, and then vacuum dried at 80°C for 3 hours to obtain anisotropic magnetic powder. The obtained anisotropic magnetic powder was Sm2Fe17 Represented by N3.

[0052] (Vibration mill process) The anisotropic magnetic powder obtained above was placed in a 500 ml metal pot containing 900 g of Φ2.5 mm beads (SUJ2) and dry-pulverized in a vibration mill. After that, the anisotropic magnetic powder was sieved to collect only the anisotropic magnetic powder.

[0053] (2) Example 2 Anisotropic magnetic powder was prepared in the same manner as in Example 1, except that in the mixing step, a magnetite slurry having an average particle size of 0.31 μm and a samarium oxide slurry having an average particle size of 0.63 μm were prepared.

[0054] (3) Example 3 (Mixing process) 2000 kg of ferrous sulfate (FeSO4) with an iron concentration of 8% was added to 988 kg of pure water, and 25% caustic soda was added while stirring until the pH reached 10.5 to create an iron hydroxide slurry. After heating this iron hydroxide slurry to 70-80°C, aeration was performed while controlling the pH to 7.5-8.5, and a slurry containing 221.3 kg of magnetite (Fe3O4) with an average particle size of 0.20 μm was created as iron oxide particles.

[0055] While stirring 74.7 kg of pure water, 74.7 kg of samarium oxide (Sm2O3) was dissolved little by little to avoid aggregation, to prepare a samarium oxide slurry. The samarium oxide particles in the slurry were then pulverized until the average particle size was 0.70 μm.

[0056] The samarium oxide slurry was added to the magnetite slurry, stirred, and precisely mixed with a bead mill (bead diameter 0.1 mm) to produce an oxide slurry in which iron and samarium were uniformly mixed at a micro level. This oxide slurry was washed with pure water until the drainage conductivity was 30 μS / cm or less.

[0057] While stirring 400 kg of pure water, 80 kg of calcium hydroxide was dissolved in small amounts at a time so as not to cause aggregation, to prepare a calcium hydroxide slurry. The calcium hydroxide particles in this slurry were then pulverized until the average particle size was 0.50 μm.

[0058] This calcium hydroxide slurry was added to the previously washed oxide slurry, stirred, and precisely mixed in a bead mill (bead diameter 0.1 mm) to create an oxide slurry in which iron, samarium, and calcium hydroxide were mixed uniformly at a micro level. The slurry was then dehydrated to a solids concentration of 30-50%, and the slurry was highly concentrated. The highly concentrated oxide slurry was pumped and spray-dried at approximately 250°C, yielding 376 kg of black Fe, Sm, and Ca mixed oxide.

[0059] (Pretreatment process) The oxide powder (376 kg) obtained above was reduced in a hydrogen reduction furnace at about 800° C. to reduce the oxygen concentration in the powder to 5.8 mass % or less, and 315 kg of hydrogen-reduced powder was recovered.

[0060] Thereafter, the SmFe was subjected to the reduction process, nitriding process, water washing process, and vibration mill process under the same conditions as in Example 1. 17 N3 anisotropic magnetic powder was prepared.

[0061] (4) Comparative Example 1 Anisotropic magnetic powder was prepared in the same manner as in Example 1, except that in the mixing step, a magnetite slurry having an average particle size of 0.15 μm and a samarium oxide slurry having an average particle size of 1.1 μm were prepared.

[0062] (5) Comparative Example 2 Anisotropic magnetic powder was prepared in the same manner as in Example 1, except that in the mixing step, a magnetite slurry having an average particle size of 0.22 μm and a samarium oxide slurry having an average particle size of 1.6 μm were prepared.

[0063] (6) Comparative Example 3 1000 kg of ferrous sulfate with an iron concentration of 8% and 1000 kg of ferric sulfate (Fe2(SO4)3) with an iron concentration of 8% were added to 988 kg of pure water, and 25% caustic soda was added while stirring until the pH became 9.2, and the mixture was aged at 70 to 80°C to produce a magnetite slurry with an average particle size of 0.05 μm. Anisotropic magnetic powder was produced in the same manner as in Example 1, except that the mixture was then mixed with a samarium oxide slurry with an average particle size of 0.59 μm.

[0064] (7) Comparative Example 4 While stirring 550 kg of pure water, 221 kg of magnetite with an average particle size of about 5 μm was dissolved little by little so as not to form lumps, to prepare a magnetite slurry. This slurry was pulverized in a bead mill until the average particle size became 1.3 μm. Then, anisotropic magnetic powder was prepared in the same manner as in Example 1, except that a slurry of samarium oxide with an average particle size of 0.72 μm was prepared.

[0065] (8) Comparative Example 5 Anisotropic magnetic powder was prepared in the same manner as in Comparative Example 4, except that in the mixing step, a magnetite slurry having an average particle size of 0.68 μm and a samarium oxide slurry having an average particle size of 0.77 μm were prepared.

[0066] (9) Comparative Example 6 (melting process) 1500 kg of pure water was heated to 35°C, 2000 kg of ferrous sulfate with an iron concentration of 8% and 20 kg of 70% sulfuric acid were added, and then 74.7 kg of samarium oxide was added and mixed to dissolve. Ammonia water was then added until the pH was 2.0 and the mixture was thoroughly stirred to completely dissolve. Pure water was added to adjust the concentration so that the total amount of the solution was 4766 kg, and this was used as the metal solution.

[0067] (Reaction process) Next, 4766 kg of the 35°C metal solution obtained above was added to 2500 kg of pure water kept at a temperature of 35°C over a period of 70 minutes, while adjusting the pH to 7-8 with 18% ammonia and carbon dioxide gas. This resulted in the formation of a precipitate of Fe and Sm carbonates. The precipitate obtained was in the form of a slurry.

[0068] (Cleaning process) The obtained slurry was thoroughly washed with pure water until the effluent conductivity became 150 μS / cm or less. After washing with , it was dried in vacuum at about 90 ° C. to obtain granular powders of Fe and Sm carbonates.

[0069] (Air firing process) The resulting Fe and Sm carbonate (448 kg) was calcined in air at 900 to 1100°C to obtain 309 kg of a reddish-brown Fe, Sm composite oxide.

[0070] The above oxide was subjected to the pretreatment process and subsequent processes of Example 1 to produce anisotropic magnetic powder.

[0071] (10) Evaluation of magnetic properties The anisotropic magnetic powders obtained in the above examples and comparative examples were filled into a sample container together with paraffin wax, and the paraffin wax was melted in a dryer, after which the easy magnetic domains were aligned in an orienting magnetic field of 16 kA / m. The magnetically oriented sample was pulse-magnetized in a magnetizing magnetic field of 32 kA / m, and the residual magnetic flux density (σr), coercive force (iHc), and squareness ratio (HK) were measured using a VSM (vibrating sample magnetometer) with a maximum magnetic field of 16 kA / m.

[0072] (11) Evaluation of the mixed distribution of iron oxide and samarium oxide The coefficient of variation of the mixed distribution was determined by dividing the backscattered electron image (5000x) of the mixture obtained in the mixing process into 24 squares with a corner equivalent to 4 μm, calculating the Fe and Sm area ratio for each square from these squares, and determining the variation in the area ratio. A field emission scanning electron microscope (SU8230, Hitachi High-Technologies, 3.0 KV, 5000x) was used for the imaging. To calculate the variation in the area ratio, the brightness of the obtained image was converted into three values ​​within the range of 0 to 255 degrees using a macro created in Excel: less than 70 degrees, 70 degrees or more and less than 170 degrees, and 170 degrees or more. The images were color-coded in descending order of brightness with white, light blue, and black, and identified as samarium oxide particles, iron oxide, and background, respectively. These were cut into 4 μm squares, and the area of ​​each color was measured using the image analysis software ImageJ, and the variation in the white and light blue area ratio was quantified using CV (%) for evaluation.

[0073] (12) SEM image of anisotropic magnetic powder The magnetic powders obtained in Example 1 and Comparative Examples 1 to 6 were photographed with a scanning electron microscope (SU3500, Hitachi High-Technologies, 5KV, 5000x). The results are shown in Figures 1 to 7. Compared to Comparative Examples 1 to 6, the magnetic powder of Example 1 had round particles with uniform particle size and good magnetic properties.

[0074] (13) Magnetic properties Table 1 shows the magnetic properties of the anisotropic magnetic powders obtained in the examples and comparative examples, the particle size of the raw material particles, the mixed state of the powder particles, and the residual salt concentration in the raw material.

[0075] [Table 1]

[0076] From Table 1, the magnetic powders of Examples 1 and 2 obtained using iron oxide particles and samarium oxide particles of specific particle sizes had improved residual magnetic flux density (σr), coercive force (iHc), and squareness ratio (HK) than the magnetic powders of Comparative Examples 1 to 5. The magnetic powders of Examples 1 and 2 also had improved residual magnetic flux density (σr), coercive force (iHc), and squareness ratio (HK) compared to the magnetic powder of Comparative Example 6 obtained by oxidizing a coprecipitate of samarium and iron, followed by reduction and nitridation. The magnetic powder of Example 3, in which calcium hydroxide was mixed in the mixing process, had significantly improved coercive force (iHc) and squareness ratio (HK) than the magnetic powders of Comparative Examples 1 to 5. Although the variation in the mixed distribution was small, the reason for the deterioration of the magnetic properties in Comparative Example 3 is believed to be that the particle size of the iron oxide was small, and therefore the reduction of residual sodium salts during washing was insufficient. [Industrial Applicability]

[0077] The method for producing anisotropic magnetic powder of the present invention can produce anisotropic magnetic powder with excellent magnetic properties.

Claims

1. A step of mixing iron oxide particles having an average particle size of 0.1 μm to 0.4 μm with oxide particles of R (R is at least one selected from the group consisting of Sc, Y, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Tm, and Lu) having an average particle size of 0.5 μm to 0.8 μm to obtain a mixture; a step of heat-treating the mixture in a reducing gas atmosphere to obtain a partial oxide; obtaining alloy particles by reducing the partial oxide; and A step of obtaining an anisotropic magnetic powder by nitriding the alloy particles. A method for producing an anisotropic magnetic powder comprising the steps of:

2. 2. The method for producing an anisotropic magnetic powder according to claim 1, wherein the coefficient of variation of the mixture distribution of the mixture is 23% or less.

3. Iron oxide particles are Fe 3 O 4 is a particle, A method for producing the anisotropic magnetic powder according to claim 1 or 2.

4. The alkali metal concentration in the iron oxide particles is 200 ppm or less. A method for producing the anisotropic magnetic powder according to any one of claims 1 to 3.

5. The method for producing an anisotropic magnetic powder according to any one of claims 1 to 4, wherein R is Sm.

6. In the step of obtaining the mixture, calcium hydroxide is further mixed. A method for producing the anisotropic magnetic powder according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Samarium-iron-nitrogen alloy powder and method for producing same

    CN108701518A

  • Method for manufacturing rare-earth-iron-nitrogen magnetic powder, and rare-earth-iron-nitrogen magnetic powder obtained thereby

    JP2003221609A

  • Method for processing sm-fe-n-based magnetic powder for bond magnet and the bond magnet

    JP2003297660A

  • Method for producing magnetic powder, and magnetic recording medium

    JP2005344177A

  • Iron nitride powder and method for producing the same

    JP2016032044A